Diagnostic value of electrocardiograms to identify pericardial effusion in acute malaria: a cross-sectional study. (14th October 2021) - Kaagaard, M D; Matos, L O; Wegener, A; Holm, A E; Gomes, L C; Lima, K O; Vieira, I M; Souza, R M; Marinho, C F; Biering-Soerensen, T; Silvestre, O M; Brainin, P
Abstract: Background: Patients with acute malaria are at risk of pericarditis and may benefit from timely identification of pericardial effusion. However, diagnostic imaging tools, such as echocardiography, are not always available in malaria endemic regions. Purpose: The aim of this study is to examine the diagnostic yield of pathology in electrocardiograms (ECG) to identify pericardial effusion in acute malaria. Methods: We enrolled adult acute malaria patients in community healthcare clinics in a remote area in South America. All patients underwent ECG, echocardiography, and peripheral blood smears. We excluded patients on anti-malarial medication, suspected concomitant infection and pregnant women. All ECGs were examined for the following criteria: (i) PR-depression >0.5mm and/or ST-elevation 0.5–1mm (I, II, aVL, aVF, V2–6) (ii) PR-elevation >0.5mm (only aVR), (iii) ST/T-ratio >0.25 (only V6), (v) low voltage, defined as QRS amplitude <5 mm in limb leads or <10 mm in precordial leads, and (vi) Spodick's sign (all leads). A criterion was positive when present in ≥2 leads. Information on shortness of breath and/or chest pain was also collected. Pericardial effusion was diagnosed by echocardiography and had to be ≥0.5cm in width. Results: We included 99 non-severe malaria patients (age 40±15 years, 55% men, median parasite density 1517/mm 3, [interquartile range 528 to 6, 585/mm 3 ]) who suffered from Plasmodium vivax (n=75), falciparum (n=22 falciparum) and mixed vivax/falciparum (n=2). The ECGs showed a mean frequency of 78±16bpm, PR-interval 147±20ms, QRS 88±11ms and QT-interval 376±34ms. A total of 11 patients displayed pericardial effusion (mean width 0.9±0.3cm, n=7 vivax, n=2 falciparum, n=2 mixed). Patients with effusion were older (mean age 39 vs 53 years, P=0.003), but displayed no difference in sex, parasite density or parasite species compared to patients without pericardial effusion (P>0.05). Distribution of ECG findings and symptoms are displayed in figure 1A. PR-depression had a sensitivity and specificity for diagnosing pericardial effusion of 73% and 90%, respectively. The sensitivity and specificity for other ECG findings and clinical symptoms are displayed in Figure 1B. Conclusion: ECG findings may aid in identifying pericardial effusion in acute malaria, specifically PR depression which had a diagnostic yield of 73% sensitivity and 90% specificity. Based on this, ECG in acute malaria may improve treatment and risk stratification when echocardiography is not an option. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Foundation, Independent Research Fund Denmark